ANALISIS SIRKULASI UDARA PADA TANAMAN KOPI BERDASARKAN POLA TANAM GRAF PRISMA DAN TINGKAT KEMIRINGAN BATANG MENGGUNAKAN METODE VOLUME HINGGA - P, Moch. Avel Romanza; Dafik, D; Fatahillah, Arif (Kadikma, 2015)
Abstract. Coffee bean is one of the superior agricultural products in Indonesia. One of the factors that affect the productivity is the cropping pattern of coffee plants. A well organized cropping pattern will make a well organized air circulation which affects the productivity of coffee beans. In this research, a model of air circulation is built based on prism graph for the cropping pattern and solved by using Finite Volume Method (FVM). The model simulation process is done by using MATLAB and FLUENT software. The model is built according to the slope of stem and the temperature of coffee plantation. The temporary result of the research shows that prism graph cropping pattern results good air circulation and also gives good effect to the air circulation around the coffee plantation. The same thing happens to the effect of the slope of stem, the more upright the coffee plant is, the better air circulation and vice versa. Key Words : Coffee plants, air circulation, prism graph, Finite Volume Method (FVM)